Kinetic Studies for the Release of Hydroxychloroquine Sulphate Drug (HCQ) In-vitro in Simulated Gastric and Intestinal Medium from Sodium Alginate and Lignosulphonic Acid Blends - Reddy S, Giridhar (Trends in Sciences, 2023)
Biodegradable polymeric blends are used to study the controlled release of Hydroxychloroquine sulphate (HCQ) as the model drug used extensively in COVID-19 treatments. HCQ drug is loaded in sodium alginate (NaAlg) and lignosulphonic acid (NaLS) blends as matrix are crosslinked using calcium chloride solution. Its release is evaluated in different pH mediums of simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). The HCQ release data obtained during experimentation is used to study kinetics using different models to investigate polymeric relaxation’s drug diffusion and mechanism in water-soluble HCQ drug. The drug release mechanism best fits the Higuchi model with Fickian diffusion as the primary polymeric relaxation mechanism. HIGHLIGHTS Biodegradable polymer blends of sodium alginate and lignosulphonic acid are loaded with Hydroxychloroquine sulphate to demonstrate and evaluate drug release kinetics in simulated gastric and intestinal gastric fluid Different kinetic models are applied for experimental data to study drug diffusion and polymer relaxation mechanism. Experimental values reveal that pH medium influences drug release The hydroxychloroquine sulphate drug release for extended period in simulated fluids in-vitro proves possible usage for controlled drug delivery applications GRAPHICAL ABSTRACT